P-002 Carotid stenting in acute stroke. (12th July 2011) - Singh, P; Dodd, R; Do, H; Albers, G; Lansberg, M; Schwartz, N; Marks, M
Abstract : Background and Purpose: Acute ischemic stroke due to extracranial carotid occlusion can lead to significant morbidity and mortality. It is unclear whether acute endovascular stenting of the carotid artery is efficacious and useful in improving overall outcomes. Previous and on-going thrombectomy studies have generally evaluated intracranial occlusions. We undertook this study to determine if acute carotid artery stenting can lead to successful revascularization and good clinical outcomes in this population with acute ischemic strokes at our institution. Methods: A retrospective review of all acute cervical ICA occlusions treated within 8 h of time last seen normal time was performed. 12 patients were treated between May 2008 and March 2010. Records were reviewed for an NIHSS before stent placement, and clinical outcome was determined via NIHSS and mRS at discharge, and at 60–90 days. All imaging and angiographic data were also reviewed to analyze preprocedural ischemic volumes, tandem occlusions, pre and post procedural TICI reperfusion scores, and symptomatic intracranial hemorrhage (defined by radiographic evidence of hemorrhage and a decline in NIHSS by >4 points). Results: 12 patients with a mean age of 69 (range 55–88) and a median NIHSS of 16 (range 12–23) were identified. Nine patients had tandem lesions with cervical occlusion and intracranial thrombus. The cervical occlusions were due to atherosclerosis (10 patients) or dissection (2 patients). All patients had initial stent placement followed by the use of an approved thrombectomy device to treat intracranial thrombus in the nine patients with intracranial thrombus. 11 of the 12 patients (92%) were successfully revascularized (TICI 2A or better). One patient was lost to follow-up. Following revascularization there were two patients with symptomatic intracranial hemorrhage. Four of the remaining 11 patients (36%) had a mRS of <2 at 60–90 days. Four of the 11 patients died in the hospital from stroke related causes. Mean age of patients with a mRS of <2 was 60 (range 46–63), whereas the mean age of patients with a mRS of >3 was 74 (range 55–88). The median initial NIHSS of patients with a mRS of <2 was 14, whereas the median NIHSS of patients with a mRS of >3 was 17. Conclusion: Emergent carotid stenting for acute ICA occlusion has a high rate of revascularization in our cohort of patients and may improve outcomes in a select group of patients with acute ischemic stroke. Patients who were younger and had lower initial NIHSS appear to have more favorable outcomes.